Transaction Management Model for Mobile Database - Al-Khinalie, Ziyad Tariq Abdul-Mehdi (2006)
Transaction support is crucial in mobile data management. Specific characteristics of mobile environments (e.g. variable bandwidth, disconnections, and limited resources on mobile hosts) make traditional transaction management techniques no longer appropriate. This is due the fact that the Atomicity, Consistency, Isolation and Durability (ACID) properties of transactions are not simply followed, in particular the consistency property. Thus, transaction management models adopting weaker form of consistency are needed and these models can now tolerate a limited amount of consistency. As a result, several transaction management models for mobile databases have been proposed, each of which has attempted to overcome some issues pertaining to transaction processing in mobile environment. However, issues such as (a) only one mobile host (MH) is allowed to update the data item (b) large number of rejected transactions (c) commit time execution of transactions at mobile host (MH) is large are not well handled. The proposed the model with the aims at solving the stated issues. The main idea underlying the model is that transaction execution can be done at the base station (BS) and mobile host (MHs). Transactions at a MH can update data locally and then precommit. When the MH connects to the BS, these pre-committed transactions are sent to the BS and re-executed as base transactions (BT) to maintain data consistency at the BS. BTs are serialized on the master data stored at the BS. This will results in data consistency. The availability of data item at MHs makes the execution of transaction at MHs possible. Each MH is allocated some value of data item, and the rest of it is kept at the base server. By having the own this resource, a transaction at a MH is allowed to update the data item within the limit of iSi. The model has been implemented and the result has shown that the model works correctly as expected.